Mathematical Modeling of the Effect of Adiantum philippense Extracts on Biofilms Formation, Adhesion with E. coli Activities Against Foodborne Pathogens (Journal of Environmental Microbiology and Toxicology, 2020)
In the quest for novel bioactive metabolites, which can also be used as therapeutic agents, Adiantum philippense (A. philippense), an ethnomedical important fern, has become a fascinating herb. In this study, the predictive mathematical modelling of A. philippense crude extract was tested against E. coli, a common food pathogen for its phytochemical constituents, antagonistic ability, and effect on bacterial adhesion and biofilm formation was calculated. For the first time in this paper we present various kinetics models such as von Bertalanffy, Baranyi-Roberts, modified Schnute, Modified Richards, Modified Gompertz, Modified Logistics and Huang were used to get values for the above kinetic constants or parameters. von Bertalanffy of the entire model was found to be the best model with the highest adjusted R2 value with the lowest RMSE value. The accuracy and bias factors values were close to unity (1.0). The parameters obtained from Von Bertalanffy model for E. coli and chloramphenicol when compared with control values were the K 1.146 (95% C.I. 1.050 - 1.241) and 0.912 (95% C.I. 0.783 – 1.041), A 0.831 (95% C.I. 0.669 – 0.994) and 0.699 (95% C.I. 0.519 – 0.880) Km 1.146 (95% C.I. 0.746 – 1.546) and 1.210 (95% C.I. 0.478 – 1.942) respectively. This shows that A. philippense was active against E. coli.
Keywords: Adiantum philippense; Biofilm; Chloramphenicol; growth curve; von Bertalaffy